Deskripsi pemberdayaan masyarakat dalam pemberian ASI eksklusif di puskesmas kota wilayah selatan Kota Kediri - Ulfah, Nurnaningsih Herya (2016)
Abstract: Kota Wilayah Selatan Public Health Center of Kediri is a public health center that had less performance achievement in the community empowerment activities of the exclusive breastfeeding, in 2010 was 67% and in 2011 was 35% of the target ≥ 80%. The objective of this study was to arrangea recommendation the community empowerment activities planning of the exclusive breastfeeding in Kota Wilayah Selatan Public Health Center of Kediri. This research was a descriptive study with cross-sectional design. Population from this research was a woman who has 6-12 month baby. This research has 123 respondent. The variables were 5 component of community empowerment. The study results showed the whole component of community empowerment of the exclusive breastfeeding that the community participation, the social functioning, the institutional development, the increased capacity and the social capital level were in the low category.